Solar chimney in tunnel considering energy-saving and fire safety. (1st November 2020) - Cheng, Xudong; Shi, Zhicheng; Nguyen, Kate; Zhang, Lihai; Zhou, Yong; Zhang, Guomin; Wang, Jinhui; Shi, Long
Abstract: Although solar chimney as a reliable passive renewable energy system has been widely adopted in buildings, its application in the tunnel is so far limited. By developing a validated numerical model, this study systematically investigated four critical factors that govern the effectiveness of solar chimney in tunnel applications, such as cavity height ( h c ), cavity gap ( L ), solar radiation, and fire size. It was known that the chimney height in tunnel shows a relatively higher impact on the natural ventilation when comparing to the applications in building, but in an opposite position for the solar radiation. The natural ventilation rate is proportional to h c 0.69 in the tunnel, but the power is between 0.5 and 2/3 for building applications. The power for solar radiation in tunnel is 0.34, where it is 0.572 for building. It was obtained from an orthogonal analysis that chimney height presents a relatively higher impact on the natural ventilation performance of a solar chimney in the tunnel, but it shows an opposite phenomenon under the smoke exhaustion model. Under both natural ventilation and smoke exhaustion modes, chimney height and cavity gap show relatively stronger influence on the performance than that from the solar radiation. A theoretical model was also developed that considers both the vertically linear and horizontally parabolic temperature distributions inside the chimney cavity. The predictions when considering both distributions agree reasonably well with those numerical results, which drops about 20.6% when comparing to the predictions of those traditional models without the considerations. Highlights: The viability of solar chimney applied in tunnel is confirmed for the first time. Typical influencing factors have been analysed to benefit the optimization design. Solar chimney can be adopted in tunnel for both energy-saving and fire safety mode. The design of solar chimney is consistent that does not lean to a single mode. A theoretical model is developed and validated considered non-uniform temperatures.